Topology optimization design related to size effect using the modified couple stress theory. Issue 1 (2nd January 2023) - Gan, Ning; Wang, Qianxuan
Abstract : Traditional topology optimization methods based on classical mechanics can provide practical design solutions for macroscale structural design. However, the rapid development of additive manufacturing, with high-resolution and rapid prototyping characteristics, has promoted their wider application in microscale or nanoscale structures. Furthermore, when the characteristic size of the macroscopic deformation field of the structure is reduced to the microscale or nanoscale, the size effect causes the structure's mechanical response to be inconsistent with the macroscale structure. Owing to the lack of microscopic characteristic parameters in the constitutive model, the traditional topology optimization framework based on the classical mechanics framework cannot accurately describe the size effect. To solve the topology optimization problem related to the size effect, a general framework that combines the modified couple stress theory with the bi-directional evolutionary structural optimization (BESO) method is constructed to explore the size effect on topology optimization.